Contrastive Analysis of Adjectives Formation of Malay and Spanish: Analisis Konstrastif Pembentukan Kata Adjektif Bahasa Melayu dan Bahasa Sepanyol - Haji Mohd Nor, Mariyati; Zainon Hamzah, Zaitul Azma; Husain, Salina; Che Su, Norizan (EDUCATUM Journal of Social Sciences, 2015)
The differences between both languages are the factors that influence the process of learning Spanish. During the learning process, students always make a mistakes and errors especially in the adjectives word formation, agreement between genders and numbers and to construct sentences correctly. The mistakes and errors are the negatives aspects that have been troubling the students and need to be avoided. The variety of Spanish adjectives is the main reason why the researcher is interested to do a study about the contrastive analysis between both languages. Therefore, the objectives of the study are to identify the characteristics of adjectives for both the Malay and Spanish and to analyze the similarities and differences in the aspects of adjectives formation for both languages. This studies also attempt to help Spanish teachers and lecturers to comprehend the difficulties faced by the students throughout the learning process of Spanish especially adjectives. To achieve these objectives the researcher uses contrastive analysis by Robert Lado (1957). The adjectives features for both languages will be described systematically and compared to determine the similarities and differences between Malay language and Spanish.